1967
DOI: 10.2307/4592985
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Basis for Eradication of Measles in 1967: A Statement by the Public Health Service

Abstract: FOK CENTURIES the measles virus has maintained a remarkably stable ecological relationship with man. The clinical disease is a characteristic syndrome of notable constancy and only moderate severity. Complications are infrequent, and, with adequate medical care, fatality is rare. Susceptibility to the disease after the waning of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 0 publications
0
24
0
1
Order By: Relevance
“…Sencer et al [3] cited the 1930s report by Hedrich [4], which indicated that when a sufficient proportion of the population in Baltimore became immune (153%), epidemics did not develop. This suggested a threshold level of immunity that would protect against a measles epidemic.…”
Section: Us Measles Elimination Effortsmentioning
confidence: 97%
See 1 more Smart Citation
“…Sencer et al [3] cited the 1930s report by Hedrich [4], which indicated that when a sufficient proportion of the population in Baltimore became immune (153%), epidemics did not develop. This suggested a threshold level of immunity that would protect against a measles epidemic.…”
Section: Us Measles Elimination Effortsmentioning
confidence: 97%
“…The introduction of measles vaccine in 1963 and its subsequent widespread use resulted in a dramatic decline in the number of reported cases, from the prevaccine annual average (1953)(1954)(1955)(1956)(1957)(1958)(1959)(1960)(1961)(1962) of ∼530,000 cases to 204,136 cases in 1966 (figure 1), a decline of 160%. The dramatic decline in measles incidence led to a call for eradication of measles from the United States in 1967 [3].…”
Section: Us Measles Elimination Effortsmentioning
confidence: 99%
“…1 However, outbreaks of measles have continued to occur despite the development of live attenuated measles virus vaccines and active measles immunization programs.2-'3 This phenomenon has been attributed to the failure of a significant percentage of the population to receive immunization with live virus vaccine, improper handling of vaccine,4 '4 immunization with the simultaneous administration of immune serum globulin,2 '10 and immunization before 12-15 months of age.7-9 11-13, 15 However, if subclinical or mild reinfection occurs as has been suggested,5-'6 many cases of measles may be unrecognized, possibly accounting for the maintenance of high antibody titers of vaccinees and sporadic cases in highly immunized populations.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1966, the United States has been building fences of immunity against measles to stop the spread of the virus within and between communities and to prevent introduction of the virus from other countries, with reestablishment of indigenous transmission [2,3]. The building blocks in this fence are each susceptible individual rendered immune through vaccination with measles vaccines, which were first licensed in 1963 [4].…”
mentioning
confidence: 99%
“…There were 4 components to the measles-elimination strategy: (1) routine vaccination of young preschool children, (2) catchup vaccination of those who were unvaccinated at school entry, (3) surveillance, and (4) response to cases [10]. The underpinning of the effort was the need to achieve high levels of population immunity as a result of vaccination.…”
mentioning
confidence: 99%